2014
DOI: 10.5489/cuaj.1646
|View full text |Cite
|
Sign up to set email alerts
|

Colonic perforation during percutaneous nephrolithotomy: An 18-year experience

Abstract: Early diagnosis and conservative management of colonic perforation can minimize patient morbidity and mortality and result in excellent healing of the fistulous tract without any serious complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 16 publications
(19 reference statements)
0
20
0
Order By: Relevance
“…CP is a very rare complication of PNL that was seen in at a rate of 0.3 % in 15 cases in the largest study to date [4]. In the other case series study CP was observed in 11 (0.2 %) out of 5260 PNL cases [9]. To the best of our knowledge, our study is the largest one to date, which includes 22 patients.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…CP is a very rare complication of PNL that was seen in at a rate of 0.3 % in 15 cases in the largest study to date [4]. In the other case series study CP was observed in 11 (0.2 %) out of 5260 PNL cases [9]. To the best of our knowledge, our study is the largest one to date, which includes 22 patients.…”
Section: Discussionmentioning
confidence: 71%
“…There are some case reports and a limited number of patient series in the literature that evaluate the risk factors and present diagnosis and treatment modalities of CP related to PNL [4,[7][8][9]. Herein, to the best of our knowledge, we present our experience with the largest series of CPs as complication of PNL and discuss the diagnosis and management of this complication in light of the current literature.…”
Section: Introductionmentioning
confidence: 96%
“…The frequency is reported as 0.2% to 0.3%. [3][4][5] Risk factors were age, dilated collecting tubules, horseshoe kidney, and retrorenal colon. [6][7][8][9] In colon perforation cases, conservative management should be the first line of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Colon perforation is a rare, but dangerous, complication; its frequency occurs between 0.2% and 0.3% of the time. 2,3 Colonic perforation might have serious consequences if it is not diagnosed early. 4 …”
Section: Introductionmentioning
confidence: 99%
“…According to the Clavien-Dindo classiication of surgical complications, colonic injury is regarded as a stage IVa complication. The incidence of colon injury is reported to be 0.3-0.5%, however in a large recently reported series, AslZare et al [36] noted 11 cases in 5260 cases of PCNL. Colonic injuries are seen in patients with retro-renal colon, the prevalence of retro-renal colon in males to be 13.6% on the right and 11.9% on the left, whilst in females it was 13.4% on the right and 26.2% on the left [37].…”
Section: Ct Beyond the Diagnosis Of Stonementioning
confidence: 99%